On the effectiveness of rotational friction hinge damper to control responses of multi-span simply supported bridge to non-uniform ground motions - Shrestha, Bipin; Hao, Hong; Nazman, H.; Bi, Kaiming (Multi-Science Publishing, 2016)
Base isolation techniques have been extensively used to improve the seismic performance of the bridge structures. The decoupling of the bridge decks from the piers and abutments using rubber isolator could result in significant reduction in seismic forces transmitted to the bridge substructures. However, the isolation devices could also increase the deck displacement and thus enhance the possibility of pounding and unseating damage of bridge decks. Moreover, previous investigations have shown that pounding and unseating damages on isolated bridges exacerbate due to the spatial variation in earthquake ground motions. Recent earthquakes revealed that isolation bearing could also be damaged due to the excessive movements of decks during large earthquake events. This study proposes the use of rotational friction hinge dampers to mitigate the damages that could be induced by large displacement of bridge decks, particularly focusing on pounding and unseating damages and bearing damages. The device is capable of providing large hysteretic damping and the cost of installing the devices is relatively economical. This article presents numerical investigations on the effectiveness of these devices on a typical Nepalese simply supported bridge subjected to spatially varying ground motions. The results indicate that rotational friction hinge dampers are very effective in mitigating the relative displacement and pounding force, as well as controlling the bearing deformation and pier drift. It is also revealed that the effectiveness of the device is not significantly affected by small changes in the slip forces; thus, small variations in the optimum slip forces during the lifetime of the bridge do not warrant any adjustment or replacement of the device.